Concentrations and loads of dissolved xenobiotics and hormones in two small river catchments of different land use in Luxembourg. Issue 2 (13th March 2012) - Krein, A.; Keßler, S.; Meyer, B.; Pailler, J.‐Y.; Guignard, C.; Hoffmann, L.
Abstract The investigation focuses on the analysis of dissolved sulfonamides, tetracyclines, analgesics, anticonvulsants and hormones in surface water. Runoff event and baseflow samples were analysed in two small river catchments of different land use in Luxembourg. For most of the flood events, similar pollutant loads to those transported during 1 day with average baseflow discharge were observed. The maximum contents during flood events and the event mean concentrations are controlled by pre‐event hydro‐climatological conditions. For all substances under investigation, maximum concentrations and event mean concentrations show a decrease with raising antecedent rainfall. In addition, the interstorm and intrastorm variability of the pollutant transport was determined. Runoff generation and corresponding transport of xenobiotic compounds show a complex pattern with many interrelated processes, taking place within bedrock, soil, anthropogenic facilities and channel and in different parts of the basins under investigation. Different sources of pollutants can be identified and related to particular locations in the basin. The influence of the sewer systems is obvious. In the agricultural Mess basin, higher rainfall amounts lead to greater quantities of laterally inflowing soil water with higher concentrations of dissolved oxytetracycline. This originates from veterinary medicines administered to livestock and enters the environment through the application of organic fertilisers, especially by slurry that is applied to the fields. Copyright © 2012 John Wiley & Sons, Ltd.